Enhanced light-induced director reorientation and dye aggregation in a nematic liquid crystal - Pergamenshchik, V.M.; Gayvoronsky, V.Ya.; Yakunin, S.V.; Vasyuta, R.M.; Nazarenko, V.G.; Lavrentovich, O.D. (Functional Materials, 2006)
Our experimental and theoretical data sugges that the strong enhancement of light-induced director reorientation in a dye-doped nematic liquid crystal can be caused by aggreagation of the dye molecules.